Emotion dysregulation is associated with increased prospective risk for chronic PTSD development. (February 2020) - Pencea, Ioana; Munoz, Adam P.; Maples-Keller, Jessica L.; Fiorillo, Devika; Schultebraucks, Katharina; Galatzer-Levy, Isaac; Rothbaum, Barbara O.; Ressler, Kerry J.; Stevens, Jennifer S.; Michopoulos, Vasiliki; Powers, Abigail
Abstract: While emotion dysregulation is associated with many psychological disorders, including posttraumatic stress disorder (PTSD), it remains uncertain whether pre-existing emotion dysregulation increases individual risk for prospectively developing PTSD in the aftermath of trauma exposure. Thus, the objective of the current study was to determine whether emotion dysregulation could prospectively predict the development of chronic PTSD symptoms following a traumatic event above and beyond other known associated factors, including depressive symptoms, baseline PTSD symptoms, total traumas experienced, and exposure to interpersonal trauma. Participants (N = 135) were recruited from the emergency department (ED) at Grady Memorial Hospital in Atlanta and follow-up assessments were conducted at 1-, 3-, 6-, and 12-months following trauma exposure. Latent Growth Mixture Modeling was used to identify PTSD symptom trajectories based on symptoms assessed at 1, 3, 6, and 12 months; three trajectories emerged: "chronic", "recovery", and "resilient". For the present study, probability of chronic PTSD symptoms was used as the outcome variable of interest. Linear regression modeling showed that emotion dysregulation was significantly associated with probability of developing chronic PTSD symptoms (p = 0.001) and accounted for an additional 7% of unique predictive variance when controlling for trauma exposure, baseline PTSD, and depressive symptoms. Our findings suggest that emotion dysregulation can be used as both a predictor of chronic PTSD and as a treatment target. Thus, identifying individuals with high levels of emotion dysregulation at the time of trauma and implementing treatments designed to improve emotion regulation could aid in decreasing the development of chronic PTSD among these at-risk individuals. Highlights: Participants were recruited from an urban level 1 trauma center. This was a longitudinal study of the development of PTSD following acute trauma. Emotion dysregulation predicted the likelihood of developing chronic PTSD post-trauma. Prior PTSD symptoms increased risk for PTSD following new trauma exposure. Emotion dysregulation should be screened in settings serving acute trauma survivors.